Design and Speedup of an Indoor Walkthrough System - Chan, Bin; Wang, Wenping; Green, Mark (International Journal of Virtual Reality, 2000)
This paper describes issues in designing a practical walkthrough system for indoor environments. We propose several new rendering speedup techniques implemented in our walkthrough system. Tests have been carried out to benchmark the speedup brought about by different techniques. One of these techniques, called dynamic visibility, which is an extended view frustum algorithm with object space information integrated. It proves to be more efficient than existing standard visibility preprocessing methods without using pre-computed data.